Challenges in Diverse Classroom of School: Teachers' Perspectives - Sharma, Shruti (Chaturbhujeshwar Academic Journal, 2023)
The objective of this study was to explore the challenges faced by teachers in diverse school classrooms and the possible way to solve the problem from the perspective of teachers themselves. In an increasingly multicultural and inclusive educational landscape, teachers play a crucial role in teaching learning experiences for students with varying backgrounds, abilities, and needs. Through a qualitative research approach with a phenomenological design, this investigation collected data through semi-structure interviews with a sample of teachers. The findings of this study reveal several common challenges that teachers encounter in diverse classrooms. These challenges encompass issues related to classroom management, differentiation of pedagogies, language barriers, and addressing diverse learning styles. This research emphasizes the need for ongoing support and resources to help teachers navigate the challenges of diverse classrooms effectively and ensure equitable educational opportunities for all students.